History of the Tumi: A Symbol of ancient Peruvian Medicine adopted by the Peruvian College of physicians - Galán-Rodas, Edén (2012)
The tumi (too-mee) is a ceremonial instrument resembling a knife with a rectangular or trapezoid handle used in ancient times in Peru. Now it is a symbol in the logo of the Peruvian College of Physicians. It was usually thought that the tumi was mainly used for performing cranial surgery, but possibly its main use was for beheading war prisoners. We learned of its existence when a tumi was first found in Huaca Las Ventanas (an archeological site), located in Batan Grande, Poma community in Lambayeque, at the end of 1936 by Professor Julio C. Tello. The first tumi was dated somewhere between 700 to 1300 A.D.